Impact of Teacher Competence and Teaching Effectiveness on Students’ Achievement in Life Science Subject at the Upper Primary Stage - Banerjee, Sarmila; Das, Namita; Mohanty, tasi (JOURNAL OF INDIAN EDUCATION, 2014)
The quality of education goes with quality of teachers. Teacher education is a system that prepares teachers who could teach the children in schools effectively. It is grounded in the belief that teachers, not assessments, must be the cornerstone of any systematic reform directed at improving our schools. The teacher is the mediator between the knower and the known, between the learner and the subject to be learned. In the present paper, efforts are made to study the qualities of teachers required for enhancement of students’ achievement in Life Science subject. The paper also suggests the skills to be developed to become an effective and competent teacher and thus provide quality education to all children. Twenty-one schools of Birbhum and Burdwan districts of West Bengal state were selected through stratified random sampling technique for the study. Four boards under West Bengal were selected for the study; they were W.B.B.S.E., V.B, I.C.S.E. and C.B.S.E. 564 students were selected as the sample for the present study. Thirty-five teachers of Life Science from the twenty-one schools were the sample of teachers for the present study. The data were collected through Teacher Competence Scale, an Observation Schedule and an Achievement Test.